2022
DOI: 10.3390/ijerph19073850
|View full text |Cite
|
Sign up to set email alerts
|

Risk Behaviors, Family Support, and Emotional Health among Adolescents during the COVID-19 Pandemic in Israel

Abstract: We investigated the prevalence of risk behaviors among Israeli adolescents (tobacco smoking, alcohol consumption, drug use) during the COVID-19 pandemic. Associations between different risk behaviors were examined and so was whether specific characteristics could predict risk behaviors in adolescents. The study consisted of 1020 Israeli adolescents aged 15–18. Study subjects completed an online survey between the first and second lockdowns in Israel (April 2020 to September 2020). Participants reported the fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 59 publications
(66 reference statements)
1
9
0
Order By: Relevance
“…Apart from self-rated health, in which female students reported better overall health, they scored significantly lower on all other well-being measures (life satisfaction, and psychological and somatic symptoms) compared to male students. This finding is consistent with other studies showing that females consistently tend to report more mental health problems than males [ 27 , 36 , 37 , 38 ] The males’ poorer self-rated health could reflect the specific conditions of the pandemic in which social distancing restrictions have lessened their physical activity levels and increased their sedentary behavior, all which are associated with poorer health [ 39 , 40 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 91%
“…Apart from self-rated health, in which female students reported better overall health, they scored significantly lower on all other well-being measures (life satisfaction, and psychological and somatic symptoms) compared to male students. This finding is consistent with other studies showing that females consistently tend to report more mental health problems than males [ 27 , 36 , 37 , 38 ] The males’ poorer self-rated health could reflect the specific conditions of the pandemic in which social distancing restrictions have lessened their physical activity levels and increased their sedentary behavior, all which are associated with poorer health [ 39 , 40 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 91%
“…In this respect, the higher consumption of psychoactive substances can be considered a means of coping with the psychological distress, anxiety, and depression associated with the lockdown (Essau & de la Torre‐Luque, 2021; Romano et al, 2021). These at‐risk behaviors appear to be associated with low family support (Shapiro et al, 2022) and poor parent–child relationships (Kapetanovic et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting social isolation and economic uncertainty have led to a significant increase in mental health concerns [ 41 , 42 ]. Recent studies have also revealed that young people’s greatest worry during lockdown was being socially disconnected, a state that is associated with higher levels of anxiety and depressive symptoms, and lower levels of life satisfaction [ 43 , 44 ]. Despite PA and mentoring support, OMHI did not improve such concerns.…”
Section: Discussionmentioning
confidence: 99%